2021
DOI: 10.1111/rssa.12703
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Question, Respondent and Interviewer Characteristics on Two Types of Item Nonresponse

Abstract: This is an open access article under the terms of the Creative Commons Attribution-NonCommercial-NoDerivs License, which permits use and distribution in any medium, provided the original work is properly cited, the use is non-commercial and no modifications or adaptations are made.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(11 citation statements)
references
References 54 publications
0
11
0
Order By: Relevance
“…The interplay of respondent and interviewer sociodemographic characteristics and their relationship with survey data quality has also been researched: The theory of homophily and higher liking of similar persons (McPherson, Smith-Lovin and Cook 2001) explains that genderor age-matched respondent-interviewer pairs can yield data of a higher quality. However, Silber et al (2021) found no evidence of gender matching or age matching in item nonresponse.…”
Section: Surveymentioning
confidence: 72%
See 2 more Smart Citations
“…The interplay of respondent and interviewer sociodemographic characteristics and their relationship with survey data quality has also been researched: The theory of homophily and higher liking of similar persons (McPherson, Smith-Lovin and Cook 2001) explains that genderor age-matched respondent-interviewer pairs can yield data of a higher quality. However, Silber et al (2021) found no evidence of gender matching or age matching in item nonresponse.…”
Section: Surveymentioning
confidence: 72%
“…Vandenplas et al (2018) researched the interview speed and found that short (fast) interviews were associated with more SL, whereas West et al (2020) found that longer interviews were associated with a lower data quality. On the other hand, Silber et al (2021) linked respondents' disengagement and difficulties with more nonresponse and satisficing. In contrast, Lechner et al (2019) showed a positive association between survey interest and the acquiescence response style (ARS hereafter; a preference for agreeing with survey questions) and a negligible association between other people's interference and ARS.…”
Section: Surveymentioning
confidence: 99%
See 1 more Smart Citation
“…The literature mentions four main factors that affect INR: the respondent, the question (Lipps and Monsch 2022), the interviewer (Silber et al 2021), and the survey mode. In this research, we focus on effects from the respondent and in particular the survey mode.…”
Section: What Affects Item (Non-)responses?mentioning
confidence: 99%
“…When aiming to solely produce a sufficient answer to a question at hand, there are several response strategies that respondents can apply. Among those strategies of shortening the survey process are: non-differentiation of response options in matrix questions (e.g., Roßmann et al, 2018), selecting "don't know" instead of a substantial response option (e.g., Silber et al, 2021), selecting the first acceptable response option of a question (e.g., Holbrook et al, 2007), selecting mid-responses on rating scales (e.g., Kaminska et al, 2010), and speeding through the questionnaire (e.g., Zhang & Conrad, 2014). Previous research investigating satisficing response strategies in a longitudinal context has shown that experienced respondents are indeed more likely to non-differentiate their answers on matrix questions (Schonlau & Toepoel, 2015) and speed through the questionnaire without taking the time to properly process the survey tasks and form substantial and accurate answers (Zhang & Conrad, 2014).…”
Section: Survey Satisficingmentioning
confidence: 99%